ANALISIS SEMANTIK : Kajian Alternatif Tentang Makna Dan Pemaknaan Wacana - Jusuf Amir Feisal Judanegara, - (1990)
As a system, language allows no partial or disintegrated analysis. The linguistic study of its component cannot be seperated from other linguistic components as a »hole in one system. Such comprehensive and at the same time holistic study of a natural language presumes that it will provide realistic descriptive picture of a language and its components as well. Based on this assumption.and the fact that natural language is a part of a culture, the writer has executed a series of investigation and bibliographic researches on semantic theories put forward by several linguists in order to be able to construct the theory that has those characteristics. In so doing, the writer is of the expectation that the study of meaning and reference of a natural language will be coped comprehensively in one i theory construction as a whole. In the outcome of the bibliographic study the writer has observed several linguistic phenomena such as follow: semantic theories that writer has encountered have their special outstanding scientific function in their dealing with meanings of certain discourse despite of the facts that they have also their shortcomings. The theory of Conditional Truth Semantics for example is quite precise in dealing with linguistic meanings and reference of declarative statements, on the other hand